Renting a Home: Good Neighbors - Mary N. Harrison (EDIS)
Good neighbors make a good neighborhood. This document is FCS5231-01, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Reviewed: December 2005.